ANALISIS STRUKTUR NAFKAH DAN KECEPATAN EKSPANSI LAHAN RUMAH TANGGA PETANI KELAPA SAWIT - Putri, Rachmi Wildan Aghnia Meutia; Dharmawan, Arya Hadi (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2019)
The expansion of oil palm plantations is an effort to improve peoples' welfare through land clearing. This expansion led to changes in household livelihood strategies around the plantation area. Various tactics and mechanism are conducted by a household to adapt to changes in order to maintain and improve their life. The expansion of forest areas into oil palm plantations leads to changes in livelihoods structures in all layers of the farm household. Widespread of palm oil plantations cause a shock to farm household. Shock is able to be faced by utilizing file livelihood assets (natural capital, human capital, social capital, physical capital, financial capital). The purpose of this paper is to identify the expansion of plantations occurring in farm households and to livelihood structure of farm households. The method used this research is a quantitative method supported by qualitative data. The result of this research shows that the higher economic level of a farmer household, the faster expansion of oil palm farmland. The palm oil on the farm sector contributes the most income of oil palm household.Key words: expansion plantations, livelihood strategy, livelihood structureABSTRAK Ekspansi perkebunan sawit merupakan upaya peningkatan kesejahteraan masyarakat melalui pembukaan lahan. Ekspansi ini menyebabkan perubahan strategi nafkah rumah tangga sekitar kawasan. Ekspansi kawasan hutan menjadi perkebunan kelapa sawit mengakibatkan perubahan struktur nafkah pada semua lapisan rumah tangga petani. Perkebunan kelapa sawit yang meluas menimbulkan kesulitan bagi rumah tangga petani. Kesulitan tersebut dihadapi oleh rumah tangga petani dengan cara memanfaatkan lima modal nafkah (modal alam, SDM, sosial, fisik dan finansial). Tujuan dari penulisan ini adalah untuk mengidentifikasi ekspansi perkebunan yang terjadi pada rumah tangga petani sawit dan menganalisis struktur nafkah rumah tangga petani sawit. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kuantitatif yang didukung oleh data kualitatif. Hasil dari penelitian ini adalah semakin tinggi lapisan ekonomi rumah tangga petani sawit, maka semakin cepat ekspansi lahan yang dilakukan. Sektor on farm kelapa sawit menyumbang pendapatan paling tinggi pada struktur pendapatan rumah tangga petani kelapa sawit.Kata Kunci : ekspansi perkebunan, strategi nafkah, struktur nafkah